Synthesis of Mesoporouse Silicate Molecular Sieves - Rahimi, Rahmatollah; Anbia, M.; Mohamnezhad, G.H.; Raban, M. (Asian Journal of Chemistry, 2010)
In this studies, surfactant hegzadesil 3-methyl ammonium chloride was used as a structural informant or mould for synthesis of mesoporous silicate molecular sieves. Many of the mesoporous titanium silicates were synthesized by adding titanium compounds to the mixture, but considerable ratio of titanium centers placed in the frame are not accessible. This disadvantage was compensated by titanium butoxide as a titanous compound after being linked to the interior surfaces of host mesoporous. The mesoporous silicate was synthesized by, S+I– method and then titanium was linked into the cavities. The structure of synthesized compound was characterized and studied by using XRD, XRF, TGA, SEM, IR techniques and surface adsorption of nitrogen. The results showed the formation of meso structure with hexagonal cavities, high surface area, isomorphic cavities, spherical morphology, functional groups and the amount of titanium input into the structure.